Computational modelling of an Organic Rankine Cycle (ORC) waste heat recovery system for an aircraft engine - Saadon, Syamimi (E D P Sciences, 2018)
Escalating fuel prices and carbon dioxide emission are causing new interest in methods to increase the thrust force of an aircraft engine with limitation of fuel consumption. One viable means is the conversion of exhaust engine waste heat to a more useful form of energy or to be used in the aircraft environmental system. A onedimensional analysis method has been proposed for the organic Rankine cycle (ORC) waste heat recovery system for turbofan engine in this paper. The paper contains two main parts: validation of the numerical model and a performance prediction of turbofan engine integrated to an ORC system. The cycle is compared with industrial waste heat recovery system from Hangzhou Chinen Steam Turbine Power CO., Ltd. The results show that thrust specific fuel consumption (TSFC) of the turbofan engine reach lowest value at 0.91 lbm/lbf.h for 7000 lbf of thrust force. When the system installation weight is applied, the system results in a 2.0% reduction in fuel burn. Hence implementation of ORC system for waste heat recovery to an aircraft engine can bring a great potential to the aviation industry.